Rethinking Green Building Through Traditional Wisdom: A Comparative Study of Greenship Certification and Indonesian Vernacular Architecture - Hanifah Hestyas Khumaira (Publication of the International Journal and Academic Research, 2025)
In responding to big contributions of construction sector to global emission, Indonesia has developed Greenship as green building rating systems tools to promote sustainable construction. In the other hand, Indonesia also has a long tradition of vernacular architecture which embody sustainability through cultural, ecological, and spiritual values. This study adapts comparative case study approach in examined the alignment and divergence between Greenship criteria and the sustainability practices embedded in the vernacular house cases. The findings reveals that site development, user comfort and material consideration in vernacular practices was resonance towards Greenship. However, the mismatches in context-responsive design especially in structural durability and passive design strategy embedded in vernacular architecture have not been fully explored in modern context. By juxtaposing modern certification standards with traditional practices, this research suggests for an elaboration between green certification and vernacular architecture value to promotes better sustainability practice.